Comparing hydrazine-derived reactive groups as inhibitors of quinone-dependent amine oxidases - Ashley A. Burke; Elizabeth S. Severson; Shreya Mool; Maria J. Solares Bucaro; Frederick T. Greenaway; Charles E. Jakobsche (Taylor & Francis Group, 2017)
Lysyl oxidase has emerged as an important enzyme in cancer metastasis. Its activity has been reported to become upregulated in several types of cancer, and blocking its activity has been shown to limit the metastatic potential of various cancers. The small-molecules phenylhydrazine and β-aminopropionitrile are known to inhibit lysyl oxidase; however, issues of stability, toxicity, and poorly defined mechanisms limit their potential use in medical applications. The experiments presented herein evaluate three other families of hydrazine-derived compounds - hydrazides, alkyl hydrazines, and semicarbazides - as irreversible inhibitors of lysyl oxidase including determining the kinetic parameters and comparing the inhibition selectivities for lysyl oxidase against the topaquinone-containing diamine oxidase from lentil seedlings. The results suggest that the hydrazide group may be a useful core functionality that can be developed into potent and selective inhibitors of lysyl oxidase and eventually find application in cancer metastasis research.